Domestic and industrial waste - local and global issues - Singh, Naresh (Caribbean Environmental Health Institute CastriesLC, 1989)
Examines the priority problems and issues on the subject of waste management. Considers the international trade in wastes and focusses on the major Caribbean waste management problems viz. sewage and excreta disposal, solid waste and hazardous wastes. Identifies two approaches to the overall management of wastes noting the prerequisites which must be met if the suggested approaches are to be economically implemented